An Overview of Aquifer Physiognomies and the δ18O and δ2H Distribution in the South African Groundwaters - Tamiru A. Abiye; Molla B. Demlie; Haile Mengistu (Hydrology, 2021)
A comprehensive assessment of the stable isotope distribution in the groundwater systems of South Africa was conducted in relation to the diversity in the aquifer lithology and corresponding hydraulic characteristics. The stable isotopes of oxygen (18O) and hydrogen (2H) in groundwater show distinct spatial variation owing to the recharge source and possibly mixing effect in the aquifers with the existing water, where aquifers are characterized by diverse hydraulic conductivity and transmissivity values. When the shallow aquifer that receives direct recharge from rainfall shows a similar isotopic signature, it implies less mixing effect, while in the case of deep groundwater interaction between recharging water and the resident water intensifies, which could change the isotope signature. As aquifer depth increases the effect of mixing tends to be minimal. In most cases, the isotopic composition of recharging water shows depletion in the interior areas and western arid zones which is attributed to the depleted isotopic composition of the moisture source. The variations in the stable isotope composition of groundwater in the region are primarily controlled by the isotope composition of the rainfall, which shows variable isotope composition as it was observed from the local meteoric water lines, in addition to the evaporation, recharge and mixing effects.